If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) = 6x Reorder the terms: 4(-1 + x) = 6x (-1 * 4 + x * 4) = 6x (-4 + 4x) = 6x Solving -4 + 4x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + 4x + -6x = 6x + -6x Combine like terms: 4x + -6x = -2x -4 + -2x = 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -2x = 0 Add '4' to each side of the equation. -4 + 4 + -2x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = 0 + 4 -2x = 0 + 4 Combine like terms: 0 + 4 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| y=-1000x^2+1100x-2.5 | | 4(6-6)=8 | | 4(x-4)=6x | | 3(-1-2)+6(2-4)= | | 9x-6=102 | | 5(x-2)=3(x-3) | | 5(y-4)/3=2y-5 | | 2(x+9)=24 | | 2.22m=4.4 | | -17=0.20n-20 | | -5(b+3)=-7b-1 | | x+25=-3(x-7) | | Y-8.1=20 | | 2w^2+15w+27=0 | | 7m-1=34 | | 6(3x+1)=-6x-18 | | 11h-7=-18 | | 2.5=1.3-r | | 2x-4+1= | | 3.3a=5.5b | | (25+x)(10+x)=1000 | | 9a=25b | | 8x-11=13x+15 | | 8.1-y=20 | | 18-x=(11+x)+3 | | 7x-7=2x-1 | | -2m-1=6m+1 | | 30000*12=x | | x^3-10x-21x=0 | | 4-2.5(x+5)=16 | | 5.8=x-72 | | 18-x=12+x |